2021
DOI: 10.1016/j.sjbs.2021.06.018
|View full text |Cite
|
Sign up to set email alerts
|

Moth diversity, species composition, and distributional pattern in Aravalli Hill Range of Rajasthan, India

Abstract: Moths are phytophagous, cosmopolitan, agricultural pests, night pollinators, chiefly nocturnal and potential bio-indicators. The current study will be the first report on species diversity, species composition, abundance, and distributional pattern of moth fauna in Aravalli Hill Range Rajasthan. During the survey period of 2018–2019, 758 specimens of moths were collected pertaining to 34 species, 26 genera belonging to 05 families, and 13 subfamilies from three different sites of Aravalli Hill Range. Based on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…At last, elevation gradient was an important environmental factor affecting species α diversity and β diversity [72]. The α diversity index reflected the compositional characteristics, abundance and diversity of species within the community [73][74][75]. According to earlier research, the α diversity index of bryophytes showed five trends with increasing elevation, such as increasing and then decreasing(bimodal curve), first decreasing followed by increasing, monotonically increasing, monotonically decreasing, increasing followed by decreasing [58,59,[76][77][78].…”
Section: Effects Of Different Elevation Gradients On the Diversity Of...mentioning
confidence: 99%
“…At last, elevation gradient was an important environmental factor affecting species α diversity and β diversity [72]. The α diversity index reflected the compositional characteristics, abundance and diversity of species within the community [73][74][75]. According to earlier research, the α diversity index of bryophytes showed five trends with increasing elevation, such as increasing and then decreasing(bimodal curve), first decreasing followed by increasing, monotonically increasing, monotonically decreasing, increasing followed by decreasing [58,59,[76][77][78].…”
Section: Effects Of Different Elevation Gradients On the Diversity Of...mentioning
confidence: 99%
“…As butterflies are excellent bio-indicators of ecosystem disturbances (Thomas, 2005). They are also recognised as ecological indicators that respond quickly to climatic and ecological changes and the stratification of the vegetation in terms of temperature wind, light, and humidity (Dar et al, 2021) so, studies on their diversity status, etc. Will be very useful in tracking changes in an ecosystem, particularly those caused by habitat loss, deforestation, organic and inorganic pollution which will help in the better management and conservation of butterfly fauna.…”
Section: Journal Of Insect Biodiversity Andmentioning
confidence: 99%
“…Moths are known to have the ability to serve as bio-indicator and nocturnal pollinators but an agricultural pest (Dar et al, 2021). Hawk moths or Sphinx moths are one of the largest groups of moths that belong to Sphingidae family.…”
Section: Introductionmentioning
confidence: 99%